Correlation between the density and refractive index with higher homologues 5O.m series. (23rd May 2016) - Bhattacharjee, Debanjan; Choudhury, Sandip P.; Bhattacharjee, Ayon
ABSTRACT: The density dependent refractive indices study of the higher homologues liquid crystalline compound 5O. m (m = 14, 16) is reported in this paper. The compounds are interdigitated with highly skewed alkyl chains. The density study of the sample has been done with the capillary tube method. For the refractive indices study, the extraordinary component ne and the ordinary component no of the samples were measured by the thin prism technique with He-Ne laser beam of wavelength 633 nm. These the results obtained were used to find the correlation between the density and refractive indices in both samples.